2015
DOI: 10.3389/fpls.2015.01015
|View full text |Cite|
|
Sign up to set email alerts
|

Wrinkled1 Accelerates Flowering and Regulates Lipid Homeostasis between Oil Accumulation and Membrane Lipid Anabolism in Brassica napus

Abstract: Wrinkled1 (WRI1) belongs to the APETALA2 transcription factor family; it is unique to plants and is a central regulator of oil synthesis in Arabidopsis. The effects of WRI1 on comprehensive lipid metabolism and plant development were unknown, especially in crop plants. This study found that BnWRI1 in Brassica napus accelerated flowering and enhanced oil accumulation in both seeds and leaves without leading to a visible growth inhibition. BnWRI1 decreased storage carbohydrates and increased soluble sugars to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 56 publications
3
53
0
1
Order By: Relevance
“…Our result also showed that expression of EuWRI1 did not affect total protein content in the transgenic tobacco seeds compared with WT. This result was consistent with previous reports that overexpression of WRI1 gene did not affect total protein content in the transgenic plant …”
Section: Discussionsupporting
confidence: 94%
“…Our result also showed that expression of EuWRI1 did not affect total protein content in the transgenic tobacco seeds compared with WT. This result was consistent with previous reports that overexpression of WRI1 gene did not affect total protein content in the transgenic plant …”
Section: Discussionsupporting
confidence: 94%
“…WRI1 homologs in many plant species, such as ZmWRI1 and BnWRI1, are proved to participate in lipogenesis (Shen et al, 2010;Li et al, 2015). Therefore, we speculate that the up-regulation of Glyma15g34770 (GmWRI1-like1) and Glyma08g24420 (GmWRI1-like2) may consistently enhance seed oil accumulation.…”
Section: Discussionmentioning
confidence: 90%
“…Similar to ABI4 , ABI5 was also shown to synergistically regulate the expression of DGAT1 under stress (Kong et al, ). In addition, overexpression of WRI in B. napus increased the expression of DGAT1 together with GPAT9 and LPAAT2 , although the specific promoter sequence has yet to be identified (Li et al, ). Very recently, the R2R3‐type MYB96 transcription factor was shown to regulate TAG biosynthesis by directly activating the expression of DGAT1 and PDAT1 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviation: ABI, ABSCISIC ACID INSENSTIVE; DGAT, acyl‐CoA:diacylglycerol acyltransferase; LEC, LEAFY COTYLEDON; MYB96, R2R3‐type MYB96 transcription factor; PDAT, phospholipid:diacyglycerol acyltransferase; and WRI, WRINKLED. This figure was developed based on information from reviews and research articles on transcriptional regulation of DGAT and PDAT (Baud et al, ; Kong et al, ; Lee et al, ; Li et al, ; Santos‐Mendoza et al, ; Wind et al, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%